A life dedicated to science: on the occasion of the 70th birthday of Editor-in-Chief Edmundas Kazimieras Zavadskas - Kačianauskas, Rimantas; Kaklauskas, Arturas; Skibniewski, Mirosław J.; Kaklauskas, Gintaris; Antuchevičienė, Jurgita; Tūpėnaitė, Laura (Journal of Civil Engineering and Management, 2014)
A life dedicated to science: on the occasion of the 70th birthday of Editor-in-Chief Edmundas Kazimieras Zavadskas. Journal of Civil Engineering and Management, 20(3), p. 311–314.